Migration and mental health - Bhugra, Dinesh; Gupta, Susham (Cambridge : Cambridge University Press, 2011)
'Human migration is a global phenomenon and is on the increase. It occurs as a result of'push' factors (asylum, natural disaster), or as a result of'pull' factors (seeking economic or educational improvement). Whatever the cause of the relocation, the outcome requires individuals to adjust to their new surroundings and cope with the stresses involved, and as a result, there is considerable potential for disruption to mental health. This volume explores all aspects of migration, on all scales, and its effect on mental health. It covers migration in the widest sense and does not limit itself to refugee studies. It covers issues specific to the elderly and the young, as well as providing practical tips for clinicians on how to improve their own cultural competence in the work setting. The book will be of interest to all mental health professionals and those involved in establishing health and social policy'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Mental health; Psychotherapy